Analytical solution of the (2+1)-dimensional Zoomeron equation by rational sine-Gordon Method - Kemaloglu, Beyhan; Yel, Gülnur; Bulut, Hasan (My University, 2024)
The current study is about the solution of the Zoomeron equation, one of the important models of mathematics and physics. In this study, the rational Sine-Gordon expansion method (RSGEM) is used to obtain various analytical solutions of the model. Compared to other methods, this method is quite effective and the desired results were obtained. Although there are many analytical solutions to the model used in the literature, we present rational type solutions for the first time with this method. We obtained rational hyperbolic function solutions, and also classified all soliton solutions (kink-like, kink, singular kink, anti-kink, dark, bright). In addition, geometric representations of the solutions in two-, and three-dimensional space and contour shape are made with the Mathematica software program.
Keywords: Analytical Method; RSGEM; Zoomeron Equation